A STUDY OF SENTENCES TYPES IN EVERYDAY IS CHRISTMAS ALBUM BY SIA - Danial, Muhammad; Zafira, Nurul Nazma; Tarihoran, Rezky Khoirina; Dewi, Ratna Sari (Fakultas Sastra UMN AL Washliyah, 2025)
English is one of the languages recognized as an international language. English brings people from all across the world together. Everyday is Christmas is Sia's eighth and debut studio album, released on November 17, 2017, by Atlantic Records and Monkey Puzzle. This study aims to examine imperative, declarative, interrogative, and exclamatory sentences, as explained above. This study adds to the scholarly debate on linguistics and improves our understanding of how sentences work within the lyrical context of Everyday is Christmas Album. For additional inquiry, employ a qualitative method by presenting data in table form and discussing the findings. Overall, this study stresses the importance of sentence patterns in English and provides insight into their use in song lyrics.